Calvarial tuberculosis - a case report - Saha, Debasish Kumar; Ahsan, ASM Areef; Fatema, Kaniz; Faruq, Mohammad Omar; Saha, Madhurima; Ahmed, Fatema (Bangladesh Critical Care Journal, 2016)
Tuberculosis is an infectious disease caused by acid fast bacilli, Mycobacterium tuberculosis that usually affects the lung although it may affect any organ. Tuberculous osteitis of the cranial bone is known as calvarial tuberculosis. The disease is considered secondary to an active or latent tuberculous lesion elsewhere in the body, but direct spread from orbit, paranasal sinuses and face has also been implicated. Though tuberculosis is endemic in Bangladesh, calvarial tuberculosis is very very rare. We report a case of a female, diabetic, hypertensive, chronic kidney disease(CKD), bronchial asthma patient presented with osteolytic lesion in skull with adjacent subcutaneous swelling. She was eventually diagnosed as calvarial tuberculosis on the basis of positive MTB- PCR from the pus aspirated from the swelling. Bangladesh Crit Care J March 2016; 4 (1): 41-43